Get messy art : the no-rules, no-judgment, no-pressure approach to making art - Grey, Caylee (Quarry Books, and imprint of The Quatro Group, 2022)
"Forget perfection-grab your supplies and get messy with the easy techniques and projects for creating with watercolor, acrylic, markers, inks, and more in Get Messy Art. Play, experiment, and explore with zero judgment, zero pressure, and all the fun"--